Rainwater harvesting for watering greenery at Polish university as a climate change adaptation strategy - Rosińska, Weronika; Przestrzelska, Kornelia; Wartalska, Katarzyna; Grzegorzek, Martyna; Wdowikowski, Marcin; Czerska, Zuzanna; Kaźmierczak, Bartosz (Bulletin of Geography. Socio-economic Series, 2025)
Considering progressive climate change and decreasing water resources, rainwater harvesting is gaining popularity as an alternative water source. This research presents the concept of sustainable rainwater management at the Wrocław University of Science and Technology (Poland). In the proposed solution, rainwater collected in a tank will be used for watering green areas. The Yield After Spillage model was used for analyzing the rainwater harvesting system operation, based on water demand (10 m3/day) and rainfall data for the 2000–2021 period. Simulations were performed for 14 tank sizes (from 10 to 140 m3). For each variant, annual needs coverage, water savings and investment costs were calculated. The results indicated that the most attractive in terms of both return period and mains water savings were tanks with intermediate capacities, with the best variant having a capacity of 60 m3 (corresponding to 6 days’ demand), allowing for mains water savings of 77.2% on average.